ERROR: ESSAY NOT FOUND COMPARING CENSORSHIP IN CHINA AND SOUTH KOREA - Nguyen, Quynh-Dan (Faculty of Law, Universitas Brawijaya, 2016)
Increasing use of Internet all over the world has made world’s communication borderless. While such condition might benefited most people, however, it invites greater risks of misinformation and opportunities for detrimental self-expression. State’s control has various degree of manners in controlling a massive flow of information. This paper will examine the current methods of internet control utilized by the governments of China and Korea, and analyze the extent to which these respective regimes impinge on the human right to freedom of opinion and expression. It begins with an overview on the international standards for freedom of expression, and the limited permissible restrictions upon the right. Furthermore, the examination of the existing legislation and regimes implemented in China and Korea, respectively, and a comparison of features such as legal grounds and practical effectiveness will be undertaken. Finally, it will discuss whether the censorship regimes implemented in China and Korea constitute legitimate restrictions upon, or impermissibly violate, the right to freedom of expression.